2011
DOI: 10.1016/j.jaac.2011.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity of the Amygdala in Early-Childhood-Onset Depression

Abstract: Objective Adult major depressive disorder (MDD) is associated with reduced cortico-limbic functional connectivity thought to indicate decreased top-down control of emotion. However, it is unclear whether such connectivity alterations are also present in early childhood onset MDD. Method Fifty-one children ages 7–11 years, prospectively studied since preschool age, completed resting state fMRI and were assigned to four groups: 1) C-MDD (N=13) personal history of early childhood onset MDD; 2) M-MDD (N=11) a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(140 citation statements)
references
References 84 publications
(80 reference statements)
13
127
0
Order By: Relevance
“…Additional processing steps included prewhitening, spatial smoothing (5-mm kernel), and registration to anatomic data and standard space (MNI 152). Amygdala RSFC maps for the left and right amygdalae were highly similar to each other; following our previous work ) and the work of others (Luking et al 2011), we conducted a second-level analysis to average the right and left amygdala RSFC maps. These mean amygdala RSFC z-score maps were used for subsequent analyses (described below).…”
Section: Neuroimaging Data Preprocessingmentioning
confidence: 92%
“…Additional processing steps included prewhitening, spatial smoothing (5-mm kernel), and registration to anatomic data and standard space (MNI 152). Amygdala RSFC maps for the left and right amygdalae were highly similar to each other; following our previous work ) and the work of others (Luking et al 2011), we conducted a second-level analysis to average the right and left amygdala RSFC maps. These mean amygdala RSFC z-score maps were used for subsequent analyses (described below).…”
Section: Neuroimaging Data Preprocessingmentioning
confidence: 92%
“…[31] This relationship between amygdala activity and mood begins early in life; amygdala reactivity to negative facial expressions has been correlated with higher severity of depression in pre-schoolers. [32] Additionally, reduced amygdala-frontal connectivity has been associated with depression in both children [33] and adult women. [34] 2.1.3.…”
Section: Mood Disorders and Amygdala Functionmentioning
confidence: 99%
“…Two previous studies examining at-risk children and adolescents found decreased connectivity between amygdala and frontal-parietal network in unaffected children of depressed mothers and in children with early onset depression (29), and decreased connectivity within the frontal-parietal cognitive control network in unaffected adolescent girls with parental depression (32).…”
Section: Introductionmentioning
confidence: 79%
“…The top-down IFG-amygdala circuitry is disrupted during emotion regulation in adults with mood disorders (66,67). A study of children with MDD and children of mothers with MDD also reported reduced negative correlation between the amygdala and lateral parietal regions including the supramarginal gyrus (29). The atypically high level of connectivity between amygdala and emotion regulation and cognitive-control regions might reflect emotion dysregulation in MDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation